Determinação da relação de novo biomarcador (IMP3) no carcinoma de nasofaringe - Ferreira, Brena Luize Cunha [UNESP] (2015)
Background: The nasopharyngeal carcinoma (NPC) is an agressive malignant epithelial neoplasm, mainly prevalent among 40-60-year-old men, with varied geographic and ethnic distribution. It is associated with Epstein Barr Virus (EBV), whose presence in the tumor cell seems to impact the prognosis. However, other factors that may be related to NPC's clinical impact and have been studied. The IMP3 biomarker, a mRNA binding protein, which has a recognized role in the tumor cell formation, has been analized as a feasible marker correlated to the overall survival of cancerpatients. Given this evidence, the object of this research isanalyze possible correlation of this biomarker to the clinical out come of these patients. Methods: To explore the IMP3 expression in the CNF patients' tumor samples seen at the Hospital das Clínicas da Faculdade de Medicina in Botucatu- UNESP, were compiled 35 cases and documented in basis of their morphological features and status of life. The immunohistochemical expression was measured and correlated with the several clinic-pathologic parameters. Results: The analysis showed high rates of relapse and mortality, also a significant number of local advanced tumors at diagnosis, and potential correlation of better prognosis with the high expression of the biomarkeranalized. Impact: A betterunderstandingof IMP3 as a biomarker, providing new routesofprognosis in nasopharynx carcinoma